Sub-micron lateral topography affects endothelial migration by modulation of focal adhesion dynamics. (24th June 2015) - Antonini, S; Meucci, S; Jacchetti, E; Klingauf, M; Beltram, F; Poulikakos, D; Cecchini, M; Ferrari, A
Abstract: Through the interaction with topographical features, endothelial cells tune their ability to populate target substrates, both in vivo and in vitro . Basal textures interfere with the establishment and maturation of focal adhesions (FAs) thus inducing specific cell-polarization patterns and regulating a plethora of cell activities that govern the overall endothelial function. In this study, we analyze the effect of topographical features on FAs in primary human endothelial cells. Reported data demonstrate a functional link between FA dynamics and cell polarization and spreading on structured substrates presenting variable lateral feature size. Our results reveal that gratings with 2 µ m lateral periodicity maximize contact guidance. The effect is linked to the dynamical state of FAs. We argue that these results are readily applicable to the rational design of active surfaces at the interface with the blood stream.